Service quality gaps and their effects on organizational performance in the real estate industry in Kenya: A case of Myspace Properties - Mutuku, Benedict; Gichinga, Lucy (International Journal of Social Sciences and Entrepreneurship, 2013)
Service quality gaps usually exist whenever a client goes to a real estate company for its services. This is because most of the time the real estate agents usually overpromise and they fail to deliver as per the promise that they made. This brings in a problem in the satisfaction of the customer which is known to be a key determinant in organizational performance. The main objective of the study was to evaluate the gaps that come about in service delivery namely the gap between consumer expectation and the management perception, the gap between management perception and quality specification, the gap between service quality specification and service delivery, the effect of the gap between external communication and the service that is delivered, the effect of the gap between expected service and experienced service and see their effect on organizational performance. The research design for the study was exploratory research design. A census of staff at MySpace properties numbering 25 was conducted. The instruments used for data collection were questionnaires which were handed to the employees and returned back. Data analysis was done through S.P.S.S program and results were presented by use of tables and graphs to show how each independent variable affect the dependent variable. The analysis showed the gaps that do exist in the property industry and specifically at MySpace properties and also recommendations were done on how best the gaps can be dealt with.
Keywords: Service quality; Service quality gaps; Organizational performance.